Chemical characterization and antimicrobial activity of hydroethanolic crude extract of Eugenia florida DC (Myrtaceae) leaves - Bastos, Renan G.; Rosa, Carla P.; Oliver, Josidel C.; Silva, Naiara C.; Dias, Amanda L. T.; Da Rocha, Cláudia Q. [UNESP]; Vilegas, Wagner [UNESP]; Da Silva, Geraldo A.; Da Silva, Marcelo A. (My University, 2016)
Objective: The present study aimed to characterize and quantify the total phenolics, flavonoids and tannins in a hydroethanolic crude extract (70% (v/v) (EB)) of the leaves of E. florida DC, as well as to evaluate the antimicrobial activity of the extract against different species of micro-organisms. Methods: EB was characterized using a mass spectrometer equipped with a direct insertion device for in-stream injection (FIA). Quantitative analyses of major compounds were carried out by spectrophotometry. In addition, we evaluated the sensitivity profiles of different strains of yeast and bacteria against different concentrations of EB. Results: The classes found were in agreement with those described in the literature: flavonoids, tannins, phenolic acids and saponins. EB showed levels of phenolic compounds, flavonoids and tannins equal to 25.82 mg gallic acid equivalents per gram of extract (EAG/g), 8.42 mg quercetin equivalents per gram of extract (EQ/g) and 7.30 mg tannic acid equivalents per gram of extract (AT/g), respectively. In the analysis of antimicrobial activity, EB was more active against yeasts but was not effective against the bacteria used in the test. Conclusion: We can conclude that E. florida DC has antimicrobial potential, due to the presence of bioactive secondary metabolites.
Keywords: Bacteria; Mass spectrometer; Micro-organisms; Phenolics; Potential; Yeasts